Methodological Description of Mapping Brazilian Long-Term Care Facilities for Older Adults - Domingues, Marisa Accioly Rodrigues da Costa (2021)
Aim: describe the methodological approach adopted to build a Brazilian database of LCTFs in the country. Methods: This exploratory research was conducted between August 2020 and 2021 based on primarily publicly accessible data. First, the database of the Sistema Único de Assistência Social for 2019 was adopted as the primary source of information. In addition, public agencies and managers were consulted and invited to share their databases. Likewise, researchers and private entities also collaborated by making their spreadsheets available. The information collected was placed in individual spreadsheets for each Brazilian state. LTCFs not catering to older adults (aged 60 and over) were excluded. Duplicate data were excluded when overlaps were identified for each new aggregated source. Results & Discussion: This brief communication describes the methodology adopted for mapping the current status of Brazilian LTCFs. Despite its caveats, this study represents an important advance in the identification, characterization, and monitoring of these services nationwide. A total of 5769 facilities were found in the 2019 SUAS census. After excluding facilities not caring for residents aged 60 or over, this total decreased to 2381 LTCFs. Consolidating and filtering the information from multiple data sources led to the identification of 7029 LTCFs for the country as a whole.